Laquinimod, a Quinoline-3-Carboxamide, Induces Type II Myeloid Cells That Modulate Central Nervous System Autoimmunity - Schulze-Topphoff, Ulf; Shetty, Aparna; Varrin-Doyer, Michel; Molnarfi, Nicolas; Sagan, Sharon A.; Sobel, Raymond A.; Nelson, Patricia A.; Zamvil, Scott S. (PLOS ONE, 2012)
Laquinimod is a novel oral drug that is currently being evaluated for the treatment of relapsing-remitting (RR) multiple sclerosis (MS). Using the animal model for multiple sclerosis, experimental autoimmune encephalomyelitis (EAE), we examined how laquinimod promotes immune modulation. Oral laquinimod treatment reversed established RR-EAE and was associated with reduced central nervous system (CNS) inflammation, decreased Th1 and Th17 responses, and an increase in regulatory T cells (Treg). In vivo laquinimod treatment inhibited donor myelin-specific T cells from transferring EAE to naive recipient mice. In vivo laquinimod treatment altered subpopulations of myeloid antigen presenting cells (APC) that included a decrease in CD11c+CD11b+CD4+ dendritic cells (DC) and an elevation of CD11bhiGr1hi monocytes. CD11b+ cells from these mice exhibited an anti-inflammatory type II phenotype characterized by reduced STAT1 phosphorylation, decreased production of IL-6, IL-12/23 and TNF, and increased IL-10. In adoptive transfer, donor type II monocytes from laquinimod-treated mice suppressed clinical and histologic disease in recipients with established EAE. As effects were observed in both APC and T cell compartments, we examined whether T cell immune modulation occurred as a direct effect of laquinimod on T cells, or as a consequence of altered APC function. Inhibition of Th1 and Th17 differentiation was observed only when type II monocytes or DC from laquinimod-treated mice were used as APC, regardless of whether myelin-specific T cells were obtained from laquinimod-treated or untreated mice. Thus, laquinimod modulates adaptive T cell immune responses via its effects on cells of the innate immune system, and may not influence T cells directly.